PENGATURAN HUKUM TERHADAP PEREMPUAN PELAKU TINDAK PIDANA PERKOSAAN - Hakim, Lukman; Prasetyawati, Endang; Yudianto, Otto (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Crime is a form of deviant behavior (crime) that is always there and is inherent in every form of society. One form of crime that occurs at this time is the act of decency or rape.